2019
DOI: 10.1155/2019/8347595
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Culture Strategies for the Expansion of Patient-Derived Cancer Stem Cell Lines

Abstract: Cancer stem cells (CSCs) have recently raised great interest as a promising biological system for designing effective cancer therapies. The scarcity of CSCs in vivo and the consequent low numbers obtained from biopsies represent a major hurdle to the development of such strategies. It is therefore necessary to design robust scalable methods to enable efficient expansion of bona fide CSCs in vitro. Here, we evaluated the applicability of computer-controlled bioreactors combined with 3D aggregate culture and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Studies have shown that CSCs can be identifed in tumors by their mammosphere formation capacity [47]. CSCs from epithelial organs can be expanded as sphere-like cellular aggregates in a serum-free medium containing epidermal growth factor and basic fbroblast growth factor [85][86][87]. In the present study, the spheres of A549-CisR cells were more numerous and larger than those of the parental cells after being cultured with the previous medium, meaning the ability to form spheres was increased after a low-dose cisplatin induction, which illustrates a more observable characteristic of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CSCs can be identifed in tumors by their mammosphere formation capacity [47]. CSCs from epithelial organs can be expanded as sphere-like cellular aggregates in a serum-free medium containing epidermal growth factor and basic fbroblast growth factor [85][86][87]. In the present study, the spheres of A549-CisR cells were more numerous and larger than those of the parental cells after being cultured with the previous medium, meaning the ability to form spheres was increased after a low-dose cisplatin induction, which illustrates a more observable characteristic of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cellular surface markers such as CD24, CD44, CD133, epithelial cell adhesion molecule (EpCAM), leucine-rich-repeat-containing G-protein-coupled receptor 5 (LGR5), and CD117 have been used to isolate CSCs from cancer cells using fluorescence-activated cell sorting (FACS) and magnetic cell sorting [ 10 , 11 , 12 , 13 ]. In addition, serum-free culture conditions supplemented with various combinations of growth factors have been applied to enrich or maintain isolated CSCs from patients diagnosed with cancer [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro 3D cell culture models using human and patient-derived CRC cell lines have been described as to be promising tools to evaluate the role of many antitumoral compounds, since these models provide cell–cell and cell–matrix interactions and, in this way, a cellular context similar to the cancer microenvironment. In particular, spheroid cultures of human CRC cells produced in stirred culture systems have been shown to be enriched in cancer stem cells and better recapitulate the in vivo tumor behavior [ 4 , 5 ]. Of note, these models have been used to ensure an accurate evaluation of the anticancer potential of phytochemicals derived from brassicas, nuts and citrus fruits [ 4 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%